Role of thermodynamic processes in plant leaf gas exchange system for assimilation of CO2 emissions from the ambient air - Sirvydas, Algimantas; Ūksas, Tomas; Kerpauskas, Paulius; Čingienė, Rasa (Journal of Environmental Engineering and Landscape Management, 2022)
When temperature in the leaf gas exchange system changes, the thermodynamic parameters describing the condition of moist air also change. A temperature change of 1 oC in plant leaf tissues leads to a change in partial water vapour pressure of 144 Pa in the gas exchange cavities. Then a temperature decrease of 1 oC in a plant leaf produces 0.897 g of condensate, from 1 m3 of air in leaf ventilation cavities on the surface. When the temperature of plant leaves in the leaf ventilation system changes, the total water vapor state on the inner surface of the leaves changes, and the water vapor state in the stomatal cavities changes. The thickness of the formed condensate film on the plant leaf canal wall surfaces depends on the canal diameter and temperature change. The paper presents information about the mechanism of water formation and thermodynamic processes in the plant leaf gas exchange system participating in the process of assimilation. The formation and change of the internal surfaces of the stomatal cavities of the water film sheet allow the participation of chemical processes in the assimilation of CO2 emissions from the environment.